Developing a church planting movement in India - Fowlkes, Dane Winstead (University of the Free State, 2004)
This dissertation acknowledges the need for Church Planting Movements among the unreached peoples of India. Of particular concern to this study is the application of Church Planting Movement strategy to forward caste Hindus of India. It traces the historical development of group or people movement strategy and then compares that strategy with traditional missionary approaches in India. It shows that evangelizing households is the primary strategy of the New Testament and the most appropriate strategy for initiating Church Planting Movements. The thesis carefully examines salvation understanding in the Hindu context and its relationship to the caste system. All of this lays a foundation for a proper approach to evangelization of forward caste Hindus in light of the fact that there have been no documented Church Planting Movements among forward caste Hindus in all of India. The paper concludes that the best approach to facilitating a Church Planting Movement among forward caste Hindus is by not planting churches. As contradictory as this sounds, the paper shows that Christian disciples remaining within Hindu culture and familial systems holds the potential for the most indigenous approach to establishing multiplying churches among forward caste Hindus.

Hierdie verhandeling beklemtoon die belangrikheid van Kerkplantbewegings onder die onbereiktes van Indië. Die hoofklem val op 'n Kerkplant-beweging strategie om die kaste Hindoes te bereik. Die geskiedenis van die groeps- en volksbewegings en strategieë word nagevors en vergelyk met tradisionele sendingbenaderings in Indië. Die evangelisering van huishoudings word in die Nuwe Testament beklemtoon en dit vorm inderdaad die uitgangspunt vir die inisiëring van Kerkgroeibewegings. Hoe die Hindoes verlossing verstaan word ondersoek in die konteks van die kaste sisteem. Dit lê die grondslag vir die aanvaarbare benadering in die evangelisering van kaste Hindoes in die lig van die feit dat daar geen gedokumenteerde verlae bestaan oor die Kerkplant-bewegings onder die ontwikkelde kaste van Indië nie Die standpunt word gestel dat die beste benadering om Kerkgroei te bevorder deur die Kerkplant- beweging onder ontwikkelde kaste juis is om nie kerke te plant nie. Teenstrydig soos dit mag voorkom, word aangetoon dat Christelike dissipels wat binne die Hindoe kuluur en gesinsgroepe bly die beste potensiaal vir die verinheemsing van die evangelie en die beste geleetheid om kerke onder ontwikkelde kaste Hindoes te laat groei, bied.
Thesis (Ph.D. (Missiology))--University of the Free State, 2004
Keywords: Church growth -- India; Church development, New -- India; Missions -- India; Evangelistic work -- India